Whole-Genome Sequence Analysis of Antimicrobial Resistance Genes in Streptococcus uberis and Streptococcus dysgalactiae Isolates from Canadian Dairy Herds - Vélez, Julián Reyes; Cameron, Marguerite; Rodríguez-Lecompte, Juan Carlos; Xia, Fangfang; Heider, Luke C.; Saab, Matthew; McClure, J. Trenton; Sánchez, Javier (Frontiers in Veterinary Science, 2017)
The objectives of this study were to determine the occurrence of antimicrobial resistance (AMR) genes using whole genome sequence (WGS) of Streptococcus uberis (S. uberis) and Streptococcus dysgalactiae (S. dysgalactiae) isolates, recovered from dairy cows in the Canadian Maritime Provinces. A secondary objective included the exploration of the association between phenotypic AMR and the genomic characteristics (genome size, guanine-cytosine content (GC), and occurrence of unique gene sequences). An initial number of 91 isolates were sequenced, and from this number, 89 were assembled. Furthermore, 16 isolates were excluded due to larger than expected genomic sizes (> 2.3 x 1,000 bp). In the final analysis, 73 were used with complete WGS and MIC records, which were part of the previous phenotypic AMR study, representing 18 dairy herds from the Maritime region of Canada, (Cameron et al., 2016). A total of 23 unique AMR gene sequences were found in the bacterial genomes, with a mean number of 8.1 (minimum: 5; maximum: 13) per genome. Overall, there were 10 AMR genes [ANT(6), TEM-127, TEM-163, TEM-89, TEM-95, Linb, Lnub, Ermb, Ermc, TetS] present only in S. uberis genomes and two genes unique (EF-TU, TEM-71) to the S .dysgalactiae genomes; 11 AMR genes [APH(3') , TEM-1,TEM-136, TEM-157,TEM-47,TetM, bl2b, gyrA, parE, phoP, rpoB] were found in both bacterial species. Two-way tabulations showed association between the phenotypic susceptibility to lincosamides and the presence of linB (P=0.002) and lnuB (P < 0.001) genes, and the between the presence of tetM (P= 0.015) and tetS (P= 0.064) genes and phenotypic resistance to tetracyclines only for the S. uberis isolates. The logistic model showed that the odds of resistance (to any of the phenotypically tested antimicrobials) was 4.35 times higher when there were > 11 AMR genes present in the genome, compared with < 7 AMR genes (P < 0.001). The odds of resistance was lower for S. dysgalactiae than S. uberis (P=0.031). When the within herd somatic cell count was > 250,000 cells/mL, a trend towards higher odds of resistance compared with the baseline category of <150,000 cell/mL was observed. When the isolate corresponded to a post-mastitis sample, there were